Cultural codes in afro-brazilian and african origin religions: geographical perceptions - do Nascimento, Taiane Flôres (Geosaberes; Vol 8 No 15 (2017): May - AugDO - 10.26895/geosaberes.v8i15.568, 2017)
Cultural Geography is one of the trends within geographic science that studies the different forms of spatialization built by man. Its focus is on the description and analysis of material and immaterial cultural codes, that is, how forms of language, religion, arts, beliefs and other cultural phenomena transform or remain constant in a certain space. In this sense, the objective of this research is to highlight the most visible cultural codes within the manifestations of afro religions, where they indicate the art of expression within the cultural code of religion. Both cultural and political manifestations are gaining strength and new spatialities have been forming in the face of numerous presentations of religions as a way of stimulating culture in space, which justifies the relevance of this research.
Keywords: Gênero, Religião, Geografia